Heterosis and genetic parameters for grain quality in oat segregating populations - Silveira,Solange Ferreira da Silveira (2016)
ABSTRACT Improvement of quality-related traits of grains is a constant concern in white oat breeding programs, which challenges breeders to understand their dynamics. The performance of different genetic combinations must be thoroughly evaluated to make high nutritional quality cultivars available. This study aimed to estimate the heterosis on F1 and F2 generations, vigor loss, due to inbreeding, and correlation between the grain chemical components to understand the dynamics of these traits, considering two segregating oat progenies. The populations Albasul × UPF 15 (population 1) and IAC 7 × UFRGS 19 (population 2) were developed. Both populations showed transgressive segregant individuals. The combination Albasul × UPF 15 provided significant heterosis for traits β-glucan total and soluble fiber contents, while the population obtained by crossing IAC 7 × UFRGS 19 generated significant gain by heterosis for total fiber, insoluble fibers and non-structural carbohydrate contents. Considering the F2 average for each population, one can observe that population 1 presents higher β-glucan and lipid contents than population 2. On the other hand, population 2 has higher protein content than population 1. In both populations, the non-structural carbohydrate content is strongly and negatively correlated whith protein, total and insoluble fibers. Correlations between total fibers and lipids and between total fibers and insoluble fibers were both positive and high in both populations.